Accumulation, juxtaposition, and no ideas but in things. Issue 3 (2nd September 2021) - John-Alder, Kathleen
Abstract: This essay explores the Passaic River Valley in New Jersey and it utilizes the concept of re-voicing discussed by literary critic James Woods to call attention to the ways certain experiences of the land legitimize the stories we tell, and, conversely, to call attention to the ways certain stories of the land legitimize the experiences we remember. Data on topography, land use, demographics, floods and chemical toxins provide factual support. Experienced-based observations on time and place by poet William Carlos Williams and artist Robert Smithson establish tone and meaning. To depict the layers of this topography and their points of intersection, the essay presents the landscape synchronically as concurrent moments in time, and diachronically as change over time. The Passaic River, in its dual role of entity, or thing, and metaphor, or meaningful idea, unites the exploration and serves as the point of focus.